2019
DOI: 10.1097/md.0000000000015792
|View full text |Cite
|
Sign up to set email alerts
|

Natural history and therapeutic strategies of post-pancreatoduodenectomy abdominal fluid collections

Abstract: Trial Design: The aim of this study was to identify independent risk factors for post-pancreatoduodenectomy (post-PD) abdominal fluid collections (AFCs) and evaluate our management protocol on it. Methods: A retrospective analysis of consecutive 2064 cases who underwent PD over the past decade in 1 single center was conducted. The patients were divided into AFCs and non-AFCs group. Univariable and multivariate logistic regression analysis was performed to identify indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…In addition, the more the patient's nutritional status declines sharply; and the nutritional status of the patient directly affects the patient's postoperative recovery. Furthermore, the smaller the inner diameter of the pancreatic duct, the more likely it is to cause pancreatic fistula, which has been confirmed by most scholars (19)(20)(21)(22). Finally, an explanation for why we included INR-PT (international normalized ratio of prothrombin time) as a risk factor in our formula, although its P value (P=0.058) is greater than 0.05, is warranted.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In addition, the more the patient's nutritional status declines sharply; and the nutritional status of the patient directly affects the patient's postoperative recovery. Furthermore, the smaller the inner diameter of the pancreatic duct, the more likely it is to cause pancreatic fistula, which has been confirmed by most scholars (19)(20)(21)(22). Finally, an explanation for why we included INR-PT (international normalized ratio of prothrombin time) as a risk factor in our formula, although its P value (P=0.058) is greater than 0.05, is warranted.…”
Section: Discussionmentioning
confidence: 61%
“…With regard to the pre-existing comorbidity of respiratory diseases, it has already been widely accepted as a significant risk factor that predisposes patients to complications ( 17 , 18 ). In addition, the larger the diameter of the tumor, the greater the probability that the tumor will invade the surrounding blood vessels, and the higher the chance of the patient's combined vascular resection and the more intraoperative blood loss ( 8 , 19 , 20 ). Moreover, intraoperative blood loss and combined vascular resection had been proved to be risk factors for post-PD complications.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that postoperative fluid collections (PFCs), detected by computed tomography (CT) scans, can predict the likelihood of developing POPF after DP 11,12 . However, several studies have also demonstrated that PFCs can be asymptomatic 13–15 . A consensus on the optimal means of integrating PFC assessment into clinical practice is lacking.…”
Section: Introductionmentioning
confidence: 99%
“… 11 , 12 However, several studies have also demonstrated that PFCs can be asymptomatic. 13 , 14 , 15 A consensus on the optimal means of integrating PFC assessment into clinical practice is lacking. Moreover, the presence of PFCs does not necessarily indicate POPF occurrence, as other factors, such as focal ascites or lymphatic leakage, may contribute to PFC.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative intra-abdominal collections (IC) are a frequent entity and could be related to postoperative complications such as anastomotic leaks (pancreatic fistula, bile leak, gastrojejunal leak), infected haematoma or undetermined intra-abdominal abscess. However, an ongoing debate exists regarding the clinical implications of postoperative intra-abdominal collections, as studies have either associated them with non-relevant complications or found no complications [ 4 ]. In the literature, ICs are not systematically reported as a separate entity, making it difficult to determine the true incidence of ICs after PD.…”
Section: Introductionmentioning
confidence: 99%